Quiz Correct answer to the quiz. check your diagnosis Pigmented paget’s disease of the nipple - Szpor, Joanna; Polak, Karina; Dyduch, Grzegorz; Okoń, Krzysztof; Hodorowicz-Zaniewska, Diana; Brzuszkiewicz, Karolina; Streb, Joanna (Polish Journal of Pathology, 2015)
Pigmented Paget’s disease of the nipple (PPD) is an uncommon variant of Paget’s disease. An accumulation of melanin within the lesion imparts a brown color to the affected area, so the lesion might clinically as well as histologically mimic melanoma. We present a case of PPD in a 60-year-old woman.